Awakeness, complexity and emergence: Learning through curriculum theory in teacher education - Richardson, Pamela; Cherkowski, Sabre; Schnellert, Leyton (Journal of the Canadian Association for Curriculum Studies, 2015)
In this self-study research, we explore how the work of significant and diverse curriculum scholars informed the learning of teacher candidates within an intensive summer semester that serves as the foundation for a Secondary Teacher Education Program (STEP) at a Canadian university. Questions that guided our inquiry include: How did teacher candidates take up and negotiate theory as part of their emerging professional identities? How did teacher candidates understand the relationship between pedagogy and their learning of/through curriculum theory? How did teacher candidates embody diverse theories and how did they understand the significance of this within and beyond this foundational semester? And finally, as teacher educators, how are our beliefs, understandings and practices developing through this self-study? We employed a qualitative, grounded theory approach and engaged in iterative cycles of analysis with learning artifacts and interview transcripts from 26 teacher candidates. We identified the rich and layered themes of emergence, complexity, and awakeness, which revealed shifts in teacher candidates’ awareness in relation to their evolving identities. We discuss these themes in relation to the above questions and locate the influences of the selected theorists. This research contributes to the field of curriculum studies through offering a living case that explores how taking up diverse and contemporary curriculum theorists has potential to both support teacher candidates to experience praxis and shift the ground of teacher education.